Correctional Programs in Reform and Rehabilitation Centers in the Southern Governorates of Palestine and Their Impact on the Level of Psychological and Social Adjustment from the Perspective of Recidivist Inmates - Reda Fayez Aldaya; Abdelrahman Ibrahim Islaieh; Rosni Samah; Myra Aidrin Mohd Ali; Ahmad Fuad Mohamad Amin (The University of Jordan, 2024)
Indexed by Scopus